2013
DOI: 10.5194/amt-6-1141-2013
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of a Cavity Attenuated Phase Shift-based extinction monitor (CAPS PMex) with an integrating nephelometer and a filter-based absorption monitor

Abstract: Abstract. An evaluation of the Cavity Attenuated Phase Shift particle light extinction monitor (CAPS PMex) using a combination of a 3-wavelength Integrating Nephelometer (NEPH) and a 3-wavelength filter-based Particle Soot Absorption Photometer (PSAP) was carried out using both laboratory-generated test particles and ambient aerosols. An accurate determination of a fixed pathlength correction for the CAPS PMex was made by comparing extinction measurements using monodisperse PSL spheres in combination with Mie … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 29 publications
4
65
0
Order By: Relevance
“…The instrument measures the extinction as an absolute instrument. This study is already published by Petzold et al (2013) and the main result is shown in Fig. 5.…”
Section: Test Of Apparent 'Accuracy For Application'supporting
confidence: 73%
“…The instrument measures the extinction as an absolute instrument. This study is already published by Petzold et al (2013) and the main result is shown in Fig. 5.…”
Section: Test Of Apparent 'Accuracy For Application'supporting
confidence: 73%
“…A method description, including results from laboratory characterization and field deployment, has been reported previously (Massoli et al, 2010). The CAPS extinction and the σ ext measured by the combination of the nephelometer and the PSAP showed a good correlation in both laboratory-generated test particles and ambient aerosols (Petzold et al, 2013). The detailed principles of the CAPS technology, optical path adjustment process, and calibration method can be found in previous studies (Kebabian et al, 2008;Kebabian and Freedman, 2007).…”
Section: Capsmentioning
confidence: 99%
“…As stated before, the technology has already been assessed both using optical closure approaches and in comparison with Mie theory (Massoli et al 2010;Petzold et al 2013b). While all previous studies were performed at ground pressure, the operation on board aircraft requires a feasibility study at low pressure.…”
Section: Laboratory Studymentioning
confidence: 99%
“…The modulation frequency is usually set to 17 kHz which provides an initial phase shift of [35][36][37][38][39][40] if the mirrors are clean. The time response of the monitor is 1-2 seconds and, according to Massoli et al (2010) and Petzold et al (2013b), its limit of detection (LOD D 3s where s is the r.m.s. noise for particle-free air) ranges between 1-3 Mm ¡1 (1 second sample period), depending on the particular instrument, and decreases as the square root of the sample period to at least 100 seconds.…”
Section: Caps Pm Ex Systemmentioning
confidence: 99%
See 1 more Smart Citation